KEBIJAKAN HOMESCHOOLING DAN RELEVANSINYA TERHADAP PENGUATAN PENDIDIKAN AGAMA ISLAM DI INDONESIA PADA ERA DIGITAL - Martina Ayu Wulandari; Zahrotutsani Mujahidah (Universitas Muhammadiyah Jember, 2024)
The purpose of this study is to analyze homeschooling policies and their relevance to strengthening Islamic religious education in Indonesia in the digital era. The approach used is a library research approach, the purpose of this approach is to gain a deep understanding of homeschooling policies and their relevance to strengthening Islamic religious education in the digital era. The results of this study show that homeschooling policies are strong, in addition to being regulated in law, homeschooling is also clearly regulated in Permendikbud No. 23 of 2006 concerning Graduate Competency Standards (SKL) and Permendikbud 129 of 2014 concerning Home School or Homeschooling. Islamic religious education through homeschooling in the digital era has a positive impact by integrating technology in the learning process. The use of applications, learning videos, and online resources has opened up new opportunities to present Islamic religious material in an engaging and interactive manner. Children can respond more actively to the material, strengthening their understanding of Islamic teachings. In addition, technology provides flexibility for parents to choose resources that fit their child's needs and development. By utilizing technology, Islamic religious learning becomes more dynamic, arouses children's interest, and creates a learning environment that is more adaptive to today's technological developments